Tooth Contact Analysis and Experimental Verification of Oerlikon Cycloidal Hypoid Gear - Du Jinfu; Fang Zongde; Yue Guiping; Gao Hongbiao; Zhao Guorui (Jixie chuandong)
A mathematical model is established for the whole tooth surface generation of the Oerlikon cycloidal hypoid gear,which includes the work flank and the tooth base surfaces,based on it,the tooth 3D model is obtained. To avoid the complicated derivation of the surface curvatures and the relative curvatures which general used to calculate the boundaries and the major axes of the contact ellipses in the past,a modified tooth contact analysis（ TCA） model is proposed which based the equations of the two mated tooth surfaces and need not to make secondary approximation,so it can correctly simulating the characteristics of the instantaneous contact area. Finally,a surface generation and TCA program is developed for Oerlikon cycloidal hypoid gear. The feasibility of this method is verified through analyzing the results obtained from Klingelnberg KIMo S5 software and the rolling test experiment,and this may serve as the foundation for loaded TCA and stress analysis.